Manajemen Holistik Pasien dengan Diagnosis Trigger Finger melalui Pendekatan Kedokteran Keluarga - Nur Syahrul Ramadhan NR; Rahim, Rosdianah; Nurdin, Abbas Zavey (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Introduction: The issue of Trigger finger has garnered increasing attention over the past few decades. The global incidence of this condition reaches 28 cases per 100,000 individuals per year, with a lifetime prevalence of 2.6% in the general population. The incidence rate increases to 5–20% in patients with comorbid diabetes mellitus. Trigger finger is more commonly found in the adult population, especially women, with an incidence 2–6 times higher than in men. This increase reflects lifestyle changes and other risk factors contributing to the occurrence of Trigger finger in various populations. Case Illustration: This report describes the case of a 33-year-old woman who experienced difficulty straightening her right thumb after it had bent, a condition she had been experiencing for three months. This complaint was accompanied by pain that worsened during her daily activities as a laundry worker. Discussion: A holistic approach to managing trigger finger through family medicine emphasizes the importance of involving various aspects of the patient's life. Treatment for trigger finger is not limited to medical interventions such as anti-inflammatory medications, corticosteroid injections, or surgery, but also includes education on ergonomics, activity modification, and physical therapy involving the role of family and community. Trigger finger, as a musculoskeletal condition, requires comprehensive management, where family support is crucial in helping patients make lifestyle changes that can prevent recurrence, such as adjusting hand use in daily activities and performing regular stretching exercises. Conclusion: In this case, the diagnosis of trigger finger was established through a thorough examination, and management was carried out holistically with a patient-centered, family-focused, and community-oriented approach. The role of family and community is essential in supporting the patient in making lifestyle changes. Planned interventions, including ergonomic adjustments and physical therapy, have proven effective, underscoring the need for a holistic approach to the sustainable management of trigger finger. Keywords: Holistic, Trigger Finger, Family Medicine